The electronic consumption in a low-income group: reports of an ethnography - Pinto, Marcelo de Rezende (Revista de Administração da UFSM, 2013)
Since the studies on consumption today occupy a position of importance in both the field of consumer research, as in the social sciences, linked to the perception that little has researched the symbolic universe of low-income individuals, we sought through this research to investigate the following question: how the experiences of consumer electronics for low-income consumers interact with the cultural and symbolic system involved in the flow of everyday social life. For this, we conducted an ethnographic study of inspiration in order to experience the daily life of consumers in their natural environment through in-depth interviews, observations and field notes. The empirical research data were examined based on content analysis. As a result, it can be noted that the experiences of consumer electronics to poor consumers can realize an intense relationship with the cultural and symbolic system built between individuals.